2013
DOI: 10.1902/jop.2013.1340014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of periodontal treatment on pregnancy outcomes

Abstract: Background: Preterm infants are at greater risk than term infants for physical and developmental disorders. Morbidity and mortality increases as gestational age at delivery decreases. Observational studies indicate an association between poor periodontal health and risk for preterm birth or low birthweight, making periodontitis a potentially modifiable risk factor for prematurity. Aim: To identify randomized controlled trials (RCTs) published between January 2011 and July 2012 and discuss all published RCTs te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 90 publications
1
8
0
1
Order By: Relevance
“…Considering these limitations and our results, the summarized evidence is insufficient to support or refute periodontal treatment for reducing adverse pregnancy outcomes. Our findings add weight to previous studies [ 25 29 ], which doubted the association between periodontal treatment and PTB or LBW found by observational studies [ 30 , 31 ]. Possible reasons for the discrepancy between results from observational studies and randomized clinical trials have been discussed elsewhere [ 25 , 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…Considering these limitations and our results, the summarized evidence is insufficient to support or refute periodontal treatment for reducing adverse pregnancy outcomes. Our findings add weight to previous studies [ 25 29 ], which doubted the association between periodontal treatment and PTB or LBW found by observational studies [ 30 , 31 ]. Possible reasons for the discrepancy between results from observational studies and randomized clinical trials have been discussed elsewhere [ 25 , 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…Although some have advocated for the use of such endpoints [38], the minimal response needed to improve glycemic control in patients with T2DM has not been determined. The periodontology community also lacks a consensus regarding the definition of “successful” treatment in terms of PD and BOP reductions [39]. Thus, we standardized treatment by requiring therapists to be trained and certified, by specifying a minimum length of treatment, and by utilizing an independent examiner to verify complete plaque and calculus removal.…”
Section: Methodsmentioning
confidence: 99%
“…However, conversely, some studies have reported nding no association between CP and preterm LBW, and that treatment for periodontitis had no effect on the prevention of LBW [55][56][57][58][59][60][61][62][63][64][65][66]. Furthermore, as LBW is related to numerous risk factors, such as the mother's age, onset of prenatal care, systemic diseases, previous LBW infants, complications during pregnancy, and term of delivery, CP may not be an important risk factor for LBW [23][24][25][26][27]67].…”
Section: Discussionmentioning
confidence: 99%